Geodynamic reconstruction of an accreted Cretaceous back-arc basin in the Northern Andes. (November 2018) - Braz, Carmen; Seton, Maria; Flament, Nicolas; Müller, R. Dietmar
Highlights: We model the opening and closure of a Cretaceous northern Andean back-arc basin. Mantle flow reconstructions are consistent with mid-mantle structure from tomography. This scenario is consistent with rollback along the extremities of wide subduction zones. Abstract: A complex history of subduction, back-arc basin formation, terrane accretion and transpressional shearing characterizes the evolution of the Caribbean and northern South American margin since Jurassic times. Quantitative plate tectonic reconstructions of the area do not include Jurassic-Cretaceous back-arc terranes of which there are both geological and geophysical observations. We developed a revised plate tectonic reconstruction based on geological observations and seismic tomography models to constrain the Jurassic-Cretaceous subduction history of eastern Panthalassa, along the western margin of the Caribbean region. This reconstruction considers the opening of a Northern Andean back-arc basin at 145 Ma, the Quebradagrande back-arc, closing at 120 Ma and followed by terrane accretion and northward translation along the South American margin starting at 100 Ma. This kinematic reconstruction is tested against two previously published tectonic reconstructions via coupling with global numerical mantle convection models using CitcomS. A comparison of modelled versus tomographically imaged mantle structure reveals that subduction outboard of the South American margin, lacking in previous tectonic models, is required to reproduce mid-mantle positive seismic anomalies imaged in P- and S-wave seismic tomography beneath South America, 500–2000 km in depth. Furthermore, we show that this subduction zone is likely produced by a back-arc basin that developed along the northern Andes during the Cretaceous via trench roll-back from 145 Ma and was closed at 100 Ma. The contemporaneous opening of the Quebradagrande back-arc basin with the Rocas Verdes back-arc basin in the southern Andes is consistent with a model that invokes return flow of mantle material behind a retreating slab and may explain why extension along the Peruvian and Chilean sections of the Andean margin did not experience full crustal break-up and back-arc opening during the late Jurassic-early Cretaceous Period.